2013
DOI: 10.1111/php.12052
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Firefly Luciferin pKa Values—Relative Absorption Intensity in Aqueous Solutions

Abstract: Ground-state vibrational analyses of firefly luciferin and its conjugate acids and bases are performed. The Gibbs free energies obtained from these analyses are used to estimate pKa values for phenolic hydroxy and carboxy groups and the N-H(+) bond in the N-protonated thiazoline or benzothiazole ring of firefly luciferin. The theoretical pKa values are corrected using the experimental values. The concentrations of these chemical species in solutions with different pH values are estimated from their corrected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(79 citation statements)
references
References 28 publications
5
74
0
Order By: Relevance
“…The experimental deduction that the protonation of a nitrogen heteroatom is responsible for the redshift in the absorption spectrum was corroborated by two theoretical computational studies 29. 30…”
Section: Photoprotolytic Cycle Of D‐luciferinmentioning
confidence: 80%
“…The experimental deduction that the protonation of a nitrogen heteroatom is responsible for the redshift in the absorption spectrum was corroborated by two theoretical computational studies 29. 30…”
Section: Photoprotolytic Cycle Of D‐luciferinmentioning
confidence: 80%
“…We have reported the molar fraction of chemical species in Fig. . Our previous study using those molar fractions showed slight discrepancies between theoretical and experimental fluorescence spectra because of overestimation of the molar fractions of N3 (N atom at 3‐position)‐protonated species.…”
Section: Methodsmentioning
confidence: 96%
“…Moreover, the widths of the absorption peaks for each chemical species were assumed to be 0.2 eV, following our previous paper , in which the theoretical absorption spectra using this width agreed well with the experimental curves. The relative absorption intensities for the photoexcitation between 350 and 600 nm in 10 nm steps were calculated by multiplying molar fractions with oscillator strengths evaluated from the Gaussian line shape with this width.…”
Section: Methodsmentioning
confidence: 99%
“…Previously reported results for the geometry optimization and vibrational analysis, which were performed using the B3LYP/aug‐cc‐pVTZ method with solvent effects, of H 2 O and H 3 O + in the S 0 state were used, because the electronic excitation of these molecules does not occur in the energy region of concern in this study .…”
Section: Methodsmentioning
confidence: 99%